2002
DOI: 10.1121/1.1424870
|View full text |Cite
|
Sign up to set email alerts
|

Effects of frequency-shifted auditory feedback on voice F0 contours in syllables

Abstract: Previous studies have shown that, during continuous vocalization, voice fundamental frequency (voice F 0 ) is modified by frequency shifted auditory feedback. In this study, the effects of frequency-shifted auditory feedback on voice F 0 contours were determined for the first two syllables of the non-sense word [tatatas]. Results show that voice F 0 is auditorily controlled with a long latency and responses are not interrupted by onset and offset of phonation itself. Furthermore, after-effects were found in vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
82
4
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 16 publications
(23 reference statements)
9
82
4
1
Order By: Relevance
“…Because both the auditory system (Pollak and Casseday, 1989;Popper andFay, 1992, 1995;Webster et al, 1992) and the vocalization system (Suga et al, 1973;Rübsamen and Schuller, 1981;Schuller and Rübsamen, 1981;Schweizer et al, 1981;Yajima and Hayashi, 1983;Rübsamen and Betz, 1986;Rübsamen and Schweizer, 1986;Gooler and O'Neill, 1987;Yajima and Larson, 1993;Jürgens, 1998Jürgens, , 2002 are separately built on common structural and functional elements in all mammals studied so far, DSC behavior is likely to share basic aspects with audio-vocal feedback control of vocal pitch in other mammals (Janik and Slater, 1997), including the involuntary response to "pitch-shifted feedback" in humans (Elman, 1981;Burnett et al, 1998;Houde and Jordan, 1998;Donath et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because both the auditory system (Pollak and Casseday, 1989;Popper andFay, 1992, 1995;Webster et al, 1992) and the vocalization system (Suga et al, 1973;Rübsamen and Schuller, 1981;Schuller and Rübsamen, 1981;Schweizer et al, 1981;Yajima and Hayashi, 1983;Rübsamen and Betz, 1986;Rübsamen and Schweizer, 1986;Gooler and O'Neill, 1987;Yajima and Larson, 1993;Jürgens, 1998Jürgens, , 2002 are separately built on common structural and functional elements in all mammals studied so far, DSC behavior is likely to share basic aspects with audio-vocal feedback control of vocal pitch in other mammals (Janik and Slater, 1997), including the involuntary response to "pitch-shifted feedback" in humans (Elman, 1981;Burnett et al, 1998;Houde and Jordan, 1998;Donath et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, DSC in horseshoe bats can provide a valuable animal model for dissecting the neural basis for auditory feedback control of mammalian vocalization and possibly vertebrates in general (Bass et al, 1997;Janik and Slater, 1997;Wild, 1997a,b;Burnett et al, 1998;Houde and Jordan, 1998;Jürgens, 1998;Donath et al, 2002). Specifically, DSC behavior in horseshoe bats has provided us with a broader appreciation for the functional significance of a prominent structure in the mammalian brainstem, the PB, which appears to be essential for something as crucial as the control of call frequencies by altered auditory feedback in echolocating horseshoe bats.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have used transient, unexpected auditory feedback perturbations to demonstrate auditory feedback control of speech. Despite being unable to anticipate the perturbation, speakers respond to pitch Donath et al, 2002;Jones and Munhall, 2002;Natke et al, 2003;Xu et al, 2004) and formant shifts (Houde and Jordan, 2002;Purcell and Munhall, 2006b) by altering their vocal output in the direction opposite the shift. These compensatory responses act to steer vocal output closer to the intended auditory target.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that subjects monitor their auditory feedback signal to regulate F 0 when producing steady vowels (Jones and Munhall, 2000), glissandos (Burnett and Larson, 2002), continuous speech (Donath et al, 2002;Xu et al, 2002), and when reading (Laukkanen, 1994). Any deviation in pitch from the intended level is corrected through a compensatory reflex, termed the pitch-shift reflex (PSR) (Burnett et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies investigating the influence of auditory feedback on voice production explored the vocal response to a single, transient shift in auditory feedback (Burnett et al, 1997;Burnett and Larson, 2002;Donath et al, 2002;Xu et al, 2002). In the present study, we examined vocal responses to continuous sinusoidal modulation in auditory feedback.…”
Section: Introductionmentioning
confidence: 99%